Visual phenomena perceived during pars plana vitrectomy under peribulbar block and monitored anaesthesia care. Issue 6 (17th September 2015) - Ramkumar, Hema L; Khatibi, Azadeh; Freeman, William R; Barteselli, Giulio; Ezon, Isaac C; Amini, Payam; Sharpsten, Lucie; Arcinue, Cheryl A; Nezgoda, Joseph T; Ferreyra, Henry A; Goldbaum, Michael H
Abstract : Aim: To investigate patients' sensory phenomena, especially instrument visualisation, and their emotional reactions during pars plana vitrectomy (PPV) under monitored anaesthesia care (MAC). Methods: One hundred adults who underwent PPV under MAC plus peribulbar block were prospectively recruited on the day after surgery to complete a questionnaire about sensory phenomena and comfort. Anaesthetics used during surgery were correlated with visual phenomena and patient comfort. Surgeons were asked to predict patient intraoperative comfort and ability to hear. Results: Of the 27% of patients who reported visual phenomena, lights (74%), colours (37%) and moving instruments (17%) were common. Instrument visualisation was not associated with any preoperative or intraoperative variables. Visual phenomena were neutrally received by 98% of patients. Neither the use of the intravenous medications during the peribulbar injection and surgery nor the type of local anaesthesia correlated with perceived level of pain. Sixty-six per cent of patients remembered hearing surgeons talk, and 96% of patients reacted neutrally to voices. Patient reports of intraoperative pain were similar to the surgeon's prediction, and mean discomfort during surgery was mild. Conclusions: The reported prevalence of intraoperative visual phenomena is low when elicited at the first postoperative visit. Surgeons can reliably predict patients' comfort, and most patients react neutrally to visual and hearing phenomena during PPV under MAC with peribulbar block. The combination of medications used may be responsible for the neutral reception of sensory phenomena.